Implementation of the Merdeka Curriculum in Elementary Schools (Case Study at SDK Pagal I, Cibal District, Manggarai, East Nusa Tenggara, Indonesia) - Laurentius Ni; Ambros Leonangung Edu; Ingrida Santriana Nice (PT. Penerbit Tiga Mutiara, 2024)
This research aims to: 1) Describe the curriculum planning, curricular, co-curricular, and extracurricular activities in the implementation of the Merdeka Curriculum. 2) Describe the implementation of the curriculum, curricular, co-curricular, and extracurricular activities in the implementation of the Merdeka Curriculum. 3) Describe the evaluation of the curriculum, curricular, co-curricular, and extracurricular activities in the implementation of the Merdeka Curriculum. This study adopts a case study approach to explore the issue in depth using qualitative methods. The techniques employed include interviews, observations, and documentation. The main respondents in this study are the principal and teachers of Grade I and IV at SDK Pagal 1, Cibal District, Manggarai, East Nusa Tenggara. The planning of the Merdeka Curriculum at SDK Pagal 1, Cibal District, has not yet reached an optimal level. The main obstacle lies in the challenges of planning co-curricular activities, where a lack of teacher understanding and limited references are the primary issues. The implementation of the Merdeka Curriculum in this school has also not reached its full potential, particularly in co-curricular activities. The evaluation of the Merdeka Curriculum’s implementation focuses more on the aspects of teaching methods, the use of learning media, the availability of adequate facilities, and challenges in executing co-curricular activities. Therefore, further implications are highly necessary to enhance and enrich the implementation of the Merdeka Curriculum in the school.